The American Association of Endocrine Surgeons Guidelines for the Definitive Surgical Management of Secondary and Tertiary Renal Hyperparathyroidism. Issue 3 (18th September 2022) - Dream, Sophie; Kuo, Lindsay E.; Kuo, Jennifer H.; Sprague, Stuart M.; Nwariaku, Fiemu E.; Wolf, Myles; Olson, John A.; Moe, Sharon M.; Lindeman, Brenessa; Chen, Herbert
Abstract : Objective: To develop evidence-based recommendations for safe, effective, and appropriate treatment of secondary (SHPT) and tertiary (THPT) renal hyperparathyroidism. Background: Hyperparathyroidism is common among patients with chronic kidney disease, end-stage kidney disease, and kidney transplant. The surgical management of SHPT and THPT is nuanced and requires a multidisciplinary approach. There are currently no clinical practice guidelines that address the surgical treatment of SHPT and THPT. Methods: Medical literature was reviewed from January 1, 1985 to present January 1, 2021 by a panel of 10 experts in SHPT and THPT. Recommendations using the best available evidence was constructed. The American College of Physicians grading system was used to determine levels of evidence. Recommendations were discussed to consensus. The American Association of Endocrine Surgeons membership reviewed and commented on preliminary drafts of the content. Results: These clinical guidelines present the epidemiology and pathophysiology of SHPT and THPT and provide recommendations for work-up and management of SHPT and THPT for all involved clinicians. It outlines the preoperative, intraoperative, and postoperative management of SHPT and THPT, as well as related definitions, operative techniques, morbidity, and outcomes. Specific topics include Pathogenesis and Epidemiology, Initial Evaluation, Imaging, Preoperative and Perioperative Care, Surgical Planning and Parathyroidectomy, Adjuncts and Approaches, Outcomes, and Reoperation. Conclusions: Evidence-based guidelines were created to assist clinicians in the optimal management of secondary and tertiary renal hyperparathyroidism.